Discrete element analysis of sand-tyre chips mixtures with different tyre chip orientations under triaxial compression tests. (15th February 2023) - Lv, Yan; Yang, Shengtao; He, Yuanyuan; Ma, Xiaozhen; Pang, Minggang; Xiong, Liangwen
Highlights: Discrete element method study on sand-tyre chips (STCh) with different tyre chip orientations is presented. Rigorous calibration procedures for obtaining the microscopic parameters of STCh mixtures are presented. The discrepancy in the reinforcement mechanism of different oriented tyre chips from a micromechanical viewpoint was studied. It provides a theoretical reference for the design of scrap tyre chips in geotechnological application. Abstract: Sand-tyre chips (STCh) mixtures are emerging civil engineering materials that have been widely studied and applied. In the sand-tyre chips system, the mechanical behavior of sand matrix is improved attributed to the excellent property of tyres. However, the effect of tyre chip orientation for STCh mixtures is not fully appreciated, especially from the microscopic scale. In this paper, the microscopic behaviors of STCh mixtures with different orientation tyre chips were investigated employing the Discrete Element Method (DEM). The tyre chips model was constructed with sufficient consideration and the microscopic parameters of STCh model were confirmed by the calibration procedure. Simulation results illustrate that horizontal tyre chips more effectively enhance the mechanical properties of mixtures. The visualization of the specimen shows that the orientation of tyre chips can influence the evolution of system contact network, formation of shear band, and bulging deformation of specimen. The microscopic mechanism including the composition of strong contacts, coordination number, average normal contact force, sliding and rolling, energy storage and dissipation, and the tensile force in tyre chips were studied to evaluate the discrepancies of different orientation tyre chips. The mechanism of the reinforcement for tyre chips can receive further understanding from this study.